PENGARUH ATRIBUT MEREK DARING PADA CITRA MEREK PERUSAHAAN DARING - , AGNI KUDANG RADITYATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many companies these days gets the benefits that is provided by online media. Ticketing business took a substantial part using online media for their marketing practice. Large amount of competitors in this business makes each company have to build their own sustainable competitive advantage. Online corporate brand images development is one to do, where its influencing attributes are ease of use, security, and customer service. Tiket.com was chosen as research object because of the company has not concerned about the importance of online corporate brand images even though Tiket.com pertained as one of the pioneers in terms of online ticketing company in Indonesia. Thus, various emerging competitors could potentially following Tiket.comâs ways to get the market. This research uses primary data. The sampling method of this research is non-probability sampling and particulary, purposive sampling type. Validity and reliability test were used to perform the instrument testing. Based on the research results, it could be posited that the improvement of ease of use, security and privacy, and customer service gives influence to improve online corporate brand images of Tiket.com. Keywords: Online Corporate Brand Images, Online Brand Attributes